Implantação de equipes autônomas em um sistema de manufatura enxuta - Cardoso Junior, Moacyr Machado; Alves, João Murta (Revista Gestão da Produção Operações e Sistemas, 2012)
The present work approaches a central question in the implementation of the philosophy of lean manufacture, which is an autonomous work team. Autonomous work teams are approached by the socio-technical school, aiming to optimize the social assembly and technician of the company. Theoretical aspects related to the teams of work, such as the question of the autonomy, flexibility, behavior, empowerment and the principles of socio-technical. The case study of a self administered autonomous team implanted at “ABC” company in a milling sector was evaluated. It was possible to verify that the implementation of the autonomous management team, despite of being still in initial phase, contributed for improvement of the productivity, quality, reduction of the waste. In what refers to the autonomy verified itself that the company gives enough emphasis to the feedback. However others important factors of the socio-technical groups are not being treated adequately. Key-words: Socio-technical Approach; Autonomy; Teams of work; Lean Manufacture.